Capacity-dependent configurations of S–CO2 coal-fired boiler by overall analysis with a unified model. (15th April 2022) - Yang, D.L.; Tang, G.H.; Li, X.L.; Fan, Y.H.
Abstract: Supercritical carbon dioxide (S–CO2 ) coal-fired power systems have been widely investigated due to its high efficiency and compactness. These power systems can range between 50 and 1000 MW and thus the corresponding boilers actually operate under dramatically different conditions. It is necessary to investigate the inherent relationship among different capacity S–CO2 boilers, which not only bring new theoretical understandings but also help improve practical designs. In this work, a unified model is proposed to investigate both thermal-hydraulic and thermodynamic performance. Furthermore, it is applied to evaluate the relationship between power capacity and boiler configuration. It is shown that small capacity furnaces suffer from overheating in the furnace wall and the optimized cooling wall is suggested to tackle this issue. Moreover, it is found that high pressure drop in the cooling wall of large capacity furnaces results in significant penalty on the cycle efficiency. For the popular 1000 MW boiler, an optimized configuration is suggested by moving the second reheating into the horizontal flue of boiler, achieving a lower pressure drop and an improved cycle efficiency from 35.4% to 50.09%. Finally, three recommendations for the capacity-dependent configurations are presented. Highlights: A unified model for different capacity S–CO2 coal-fired boilers is established. Overheating of cooling wall in boilers of small capacity is illustrated and an optimization is proposed. Pressure drop penalty worsens in cooling wall of large capacity furnaces and results in a cycle efficiency reduction. Three recommendations for the capacity-dependent configurations are demonstrated.